Genotyping-by-sequencing reveals low genetic diversity and peripheral isolation in Southern populations of Sophora koreensis, a Korean endemic shrub - Young-Ho Ha; Jong-Bin An; Jaesang Chung; Jung-Won Yoon; Hee-Young Gil (Scientific Reports)
Abstract We evaluated the patterns of genetic diversity, structure, and differentiation both within and among populations levels of Sophora koreensis in South Korean populations using the genotyping-by-sequencing method. We obtained 1,463 single nucleotide polymorphisms from 92 individuals from 12 populations. Genetic diversity analysis revealed a significant heterozygote deficiency (P < 0.001) and low levels of genetic diversity (average expected heterozygosity = 0.150, mean observed heterozygosity = 0.015, and nucleotide diversity = 0.163) in S. koreensis. Three peripheral populations (SC, SE, and SF) located at the southeastern margin of S. koreensis distribution showed lower levels of genetic diversity than other populations. Further to the population admixture results, Principal Component Analysis and barrier analyses showed clear genetic differentiation between the three peripheral populations and the other main populations. The genetic patterns and structures of the three peripheral populations were most likely a consequence of their isolation from the main populations and their small effective population sizes. Geographic and hydrological barriers between peripheral and central populations effectively interfere with gene flow among populations. Habitat protection should be strengthened for the entire distribution of S. koreensis to maintain its genetic diversity and unique genotypes, including peripheral populations.